2018
DOI: 10.3390/su10072344
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sustainability of the French Organic Rice and PGI Einkorn Value Chains: A Preliminary Assessment Based on Network Analysis

Abstract: Public authorities and consumers increasingly support food value chains that are more environmentally friendly. However, these value chains are faced with technical, economic and institutional limitations, calling into question their long-term viability. Based on two case studies of alternative food chains in France, namely einkorn (Triticum monococcum) in Haute Provence and organic rice in the Camargue, we evaluated their capacity to remain both viable and environmentally, economically and socially sustainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Attending at the lack of a clear operationalization of the concept of farm diversification, with the employment of different typologies and little consensuses on a single categorization scheme (Barbieri and Mahoney, 2009;Ferguson and Hansson, 2015), our study proposes an original framework that operationalises the farm diversification concept in conventional and unconventional terms, allowing to discriminate different profiles of farm diversification businesses. Furthermore, our work responds to recent calls for more quantitative studies about farm diversification (Garc ıa-Cornejo et al, 2020) and agricultural innovation networks (Qui edeville et al, 2018;Schoen, 2017) in unexplored contexts, conducting a survey in Portugal, a South Europe country with agricultural specificities. This study demonstrates that innovation networks, promoted by specialized agricultural advisors and R&D projects, are important forms of open innovation in the agricultural sector.…”
Section: Farm Diversification and Open Innovationmentioning
confidence: 67%
See 2 more Smart Citations
“…Attending at the lack of a clear operationalization of the concept of farm diversification, with the employment of different typologies and little consensuses on a single categorization scheme (Barbieri and Mahoney, 2009;Ferguson and Hansson, 2015), our study proposes an original framework that operationalises the farm diversification concept in conventional and unconventional terms, allowing to discriminate different profiles of farm diversification businesses. Furthermore, our work responds to recent calls for more quantitative studies about farm diversification (Garc ıa-Cornejo et al, 2020) and agricultural innovation networks (Qui edeville et al, 2018;Schoen, 2017) in unexplored contexts, conducting a survey in Portugal, a South Europe country with agricultural specificities. This study demonstrates that innovation networks, promoted by specialized agricultural advisors and R&D projects, are important forms of open innovation in the agricultural sector.…”
Section: Farm Diversification and Open Innovationmentioning
confidence: 67%
“…Furthermore, our work responds to recent calls for more quantitative studies about farm diversification (García-Cornejo et al. , 2020) and agricultural innovation networks (Quiédeville et al. , 2018; Schoen, 2017) in unexplored contexts, conducting a survey in Portugal, a South Europe country with agricultural specificities.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The concept of value chain [8] explains the value chain as an activity that occurs both internally and externally from the procurement of raw materials and processing to the delivery of goods and services [3]. More recently, value chain analysis studies have been conducted to contribute to the competitive advantage of [1], in line with the study by [9], which found that organic rice value chain is system-centered, with a variety of connections that link the process of centralized organic rice farmers as a strong network, resulting in sustainability influencing operational efficiency of the farmers. A similar study by [10] studied business strategy planning using value chain analysis, and it was found that value chains contribute to purchasing and management of materials, exports, infrastructure, marketing and sales, as well as services and other supports, considered as a great help in increasing the competitiveness of the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Value chains contribute to resource management, marketing, sales, and other services, to increase the competitiveness of organizations (Straková et al, 2020). Integration between value chains and farmer operations can result in better operational efficiencies that enable farmers to enhance competitiveness (Quiédeville et al, 2018). Value chain analysis contributes to the advancement of competitive advantage for any given product (Ferdous & Ikeda, 2018).…”
Section: Introductionmentioning
confidence: 99%